Frequently Assigned Readings in Behavior Analysis Graduate Training Programs - Pastrana, Sarah J.; Frewing, Tyla M.; Grow, Laura L.; Nosik, Melissa R.; Turner, Maria; Carr, James E. (Behavior analysis in practice, 2018)
Demand for behavior-analytic services has greatly increased in recent years, resulting in the development of many new graduate training programs. The purpose of the present study was to identify frequently assigned readings from the course syllabi of behavior-analytic training programs with the highest pass rates on the Board Certified Behavior Analyst® (BCBA®) examination. The readings are categorized by curriculum area (e.g., ethics, behaviorism, single-subject research methodology) to provide a resource for new program development and language translation efforts.